INFLUENCES OF INTERACTION BETWEEN BLADES AND TOWER AND ROTATION EFFECT ON DYNAMIC RESPONSE FOR THE LARGE-SCALE WIND TURBINE - ZHANG JianPing; SHI FengFeng (Jixie qiangdu)
The actual working wind filed was established by the self-designed programs of wind shear and Davenport wind spectrum. Taking the 5MW wind turbine built in UG as the research object,the dynamic response of the wind turbine suffered interaction between blades and tower under different rotating speed was simulated by ANSYS based on unidirectional fluidstructure interaction（ UFSI）. The results indicate that owing to the interaction effect between blades and tower,the maximum displacement and stress of the blades and tower increase to a certain extent. The coupling effect leads to the phenomenon that the maximum stress of the blades changes its location from relative span 0. 5 to 0. 7,and several maximum stresses appear in the tower area. It’s necessary to consider the combined effect between the structural coupling and rotation to obtain the accurate operating parameters of the wind turbine.